Classification of Rice Based on Statistical Analysis of Pasting Properties and Apparent Amylose Content: The Case of Oryza glaberrima Accessions from Africa. Issue 1 (19th January 2015) - Gayin, Joseph; Chandi, Gurpreet Kaur; Manful, John; Seetharaman, Koushik
ABSTRACT: The diversity of 1, 020 Oryza glaberrima rice accessions being kept at the Genetic Resources Unit of the Africa Rice Center with a varied range of apparent amylose content (AAC) and pasting properties was explored with cluster analysis. Rice cultivars are usually characterized according to grain dimensions, AACs, and gelatinization temperatures; however, this work focused on grouping African rice accessions based on their pasting properties and AAC. Using the Ward method of hierarchical cluster analysis, 1, 020 rice accessions were initially distributed into five major clusters and further into 23 subclusters. The distribution pattern indicated that clusters I, II, III, IV, and V formed 27.6, 10.2, 15.8, 23.7, and 22.6% of the entire population, respectively. Although some of the groups had similar AAC, their pasting properties were very different, making it imperative for further investigations. Peak viscosity highly correlated ( P < 0.01) with trough, breakdown, and final viscosities in all five clusters, whereas correlation between peak viscosity and AAC was not significant within clusters II and IV. Additionally, this categorization serves as a tool for exploring materials that can be employed in the development of rice cultivars for specific end uses.